2018
DOI: 10.1080/09540121.2018.1468012
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional health-related stigma in persons living with HIV and chronic pain: implications for depressive symptoms

Abstract: "Intersectional health-related stigma" (IHRS) refers to stigma that arises at the convergence of multiple health conditions. People living with HIV (PLWH) and chronic pain have two highly stigmatized health conditions, and thus may be at especially high risk for internalizing these stigmas and consequently experiencing depression. This study examined the intersectionality of internalized HIV and chronic pain stigma in relation to depressive symptoms in a sample of PLWH and chronic pain. Sixty participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
4
34
1
Order By: Relevance
“…The term “intersectionality” is often credited to Dr. Kimberlé Crenshaw () in her seminal essay proposing that the burdens Black women face are greater than that of their race or sex alone. Although it began as a legal argument, the concept of intersectionality—that one must consider the whole of a person's identities to best understand their experiences—has expanded into numerous academic and applied disciplines, including psychology (Else‐Quest & Hyde, ; Rosenthal, ; Williams & Fredrick, ), public health (Bowleg, ; Goodin et al, ), and even the common vernacular, as it was added to Webster's Dictionary in 2017 (Merriam‐Webster, ). Accordingly, researchers have recently used an intersectional approach to study discrimination (e.g., Lewis & Van Dyke, ; Liu & Wong, ; Sugarman et al, ), sexual and domestic violence (e.g., Armstrong, Gleckman‐Krut, & Johnson, ; Conwill, ; Powell, Hlavka, & Mulla, ), as well as physical and mental health (e.g., Dlugonski, Martin, Mailey, & Pineda, ; Goodin et al, ; Lewis & Van Dyke, ; Velez, Moradi, & DeBlaere, ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…The term “intersectionality” is often credited to Dr. Kimberlé Crenshaw () in her seminal essay proposing that the burdens Black women face are greater than that of their race or sex alone. Although it began as a legal argument, the concept of intersectionality—that one must consider the whole of a person's identities to best understand their experiences—has expanded into numerous academic and applied disciplines, including psychology (Else‐Quest & Hyde, ; Rosenthal, ; Williams & Fredrick, ), public health (Bowleg, ; Goodin et al, ), and even the common vernacular, as it was added to Webster's Dictionary in 2017 (Merriam‐Webster, ). Accordingly, researchers have recently used an intersectional approach to study discrimination (e.g., Lewis & Van Dyke, ; Liu & Wong, ; Sugarman et al, ), sexual and domestic violence (e.g., Armstrong, Gleckman‐Krut, & Johnson, ; Conwill, ; Powell, Hlavka, & Mulla, ), as well as physical and mental health (e.g., Dlugonski, Martin, Mailey, & Pineda, ; Goodin et al, ; Lewis & Van Dyke, ; Velez, Moradi, & DeBlaere, ), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the mean BDI score for this cohort (19; SD 8) was greater than that reported by healthy controls (9; SD 8), it was similar to another cohort of HIV-positive South Africans (17; SD 12). 21,27 It is worth considering that individuals living with both HIV and chronic pain live with two stigmatised conditions and this may have compounded both their depressive symptoms and pain intensity, 28 leading to the high scores seen here.…”
Section: Discussionmentioning
confidence: 96%
“…9,37 To illustrate, recent research completed by our study team has found that PLWH with chronic pain experience a high degree of stigma related to their chronic pain, as well as their HIV status. 19…”
Section: Discussionmentioning
confidence: 99%